A Comparative Result of Ventriculoperitoneal Shunt, Focusing Mainly on Gravity-Assisted Valve and Programmable Valve - Lee, Won-Chul (The Korean Neurosurgical Society, 2010)
OBJECTIVE: Despite rapid evolution of shunt devices, the complication rates remain high. The most common causes are turning from obstruction, infection, and overdrainage into mainly underdrainage. We investigated the incidence of complications in a consecutive series of hydrocephalic patients. METHODS: From January 2002 to December 2009, 111 patients underwent ventriculoperitoneal (VP) shunting at our hospital. We documented shunt failures and complications according to valve type, primary disease, and number of revisions. RESULTS: Overall shunt survival time was 268 weeks. Mean survival time of gravity-assisted valve (GAV) was 222 weeks versus 286 weeks for other shunts. Survival time of programmable valves (264 weeks) was longer than that of pressure-controlled valves (186 weeks). The most common cause for shunt revision was underdrainage (13 valves). The revision rate due to underdrainage in patients with GAV (7 of 10 patients) was higher than that for other valve types. Of 7 patients requiring revision for GAV underdrainage, 6 patients were bedridden. The overall infection rate was 3.6%, which was lower than reported series. Seven patients demonstrating overdrainage had cranial defects when operations were performed (41%), and overdrainage was improved in 5 patients after cranioplasty. CONCLUSION: Although none of the differences was statistically significant, some of the observations were especially notable. If a candidate for VP shunting is bedridden, GAV may not be indicated because it could lead to underdrainage. Careful procedure and perioperative management can reduce infection rate. Cranioplasty performed prior to VP shunting may be beneficial.